Timelines and Dystopian Imagery: Modernism and Realism in W.H. Auden’s "The Shield of Achilles" - Aurin, Tasmia Islam (International Journal of Language and Literary Studies, 2024)
This research item explores W.H. Auden’s amalgamation of different timelines and dystopian imagery using modernist and realist styles in “The Shield of Achilles”. The paper aims to analyze his depiction of societal evolution and human experiences. Auden braids stories of change and existential questions by combining innovative techniques with realistic details. The study deciphers the poem’s layered time periods and it’s method of combining despair and hope while straddling artistic innovation and mid-20th century realities. Auden’s dystopian images reflect the era’s anxieties, while his modernist approach challenges norms. The research item aims to bring forward the temporal layers, revealing his engagement with linear and cyclical time concepts. The study elucidates tensions between avant-garde creativity and mid-20th century existence. In essence, the goal of this study is to analyze Auden’s blending of timelines, dystopian scenes, modern and realistic styles to depict societal experiences, human sufferings including psychologically, materialistically, and lastly existential crisis. It aims to understand his panoramic view combining hope/despair and innovation/reality through close stylistic examination.